Peran Pemerintah Dan Ulama Terhadap Tinginya Angka Perceraian Di Kecamatan Stabat Kabupaten Langkat - Rasyid Al Madjid (Peduli Riset dan Pengabdian Masyarakat, 2023)
Divorce is indeed one of the events that is very scary and has a big impact on the family, especially the husband, wife and children. The causes of divorce also vary, such as failure to communicate, infidelity, domestic violence, economic problems, early marriage, cultural changes, and so on. The purpose of this method is to collect data in a natural setting, therefore it is called a naturalistic method. To achieve this goal, researchers need to go directly to the field to collect data. This type of research method is often used to develop theory and gain understanding of social phenomena. This involves collecting data from natural settings and using the researcher as the main instrument to collect data through observation, interviews and other techniques. Data description is a description of the data used in a study. In testing the description of this data, the researcher tries to find out the description or condition of the respondents who are the sample in this study. As for the factors or reasons for the parties filing a divorce case, there are several factors, the most dominant being the factor due to continuous disputes, economic factors and there are also several other factors such as leaving one of the parties.